2018
DOI: 10.1016/j.psychsport.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The role of athletic identity in the development of athlete burnout: The moderating role of psychological flexibility

Abstract: 2018) 'The role of athletic identity in the development of athlete burnout : the moderating role of psychological exibility.', Psychology of sport and exercise., 39 . pp. 45-51.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
4
23
0
2
Order By: Relevance
“…The person as a whole-and not just the athlete-will be treated with respect to his or her personal history, values, and the role of sport in his or her present and future life. Overall, Greg benefitted from psychological and behavioral flexibility by developing a constructive response to stress (Hayes, 2004), which is supported by recent research (Chang, Wu, Kuo, & Chen, 2018) suggesting that psychological flexibility prevents emotional exhaustion in subjects with high levels of athletic identity.…”
Section: Resultssupporting
confidence: 54%
“…The person as a whole-and not just the athlete-will be treated with respect to his or her personal history, values, and the role of sport in his or her present and future life. Overall, Greg benefitted from psychological and behavioral flexibility by developing a constructive response to stress (Hayes, 2004), which is supported by recent research (Chang, Wu, Kuo, & Chen, 2018) suggesting that psychological flexibility prevents emotional exhaustion in subjects with high levels of athletic identity.…”
Section: Resultssupporting
confidence: 54%
“…As children and adolescents play a particular sport, they develop an identity associated with their role as an athlete, as part of their self-concept (Brewer et al, 1993). However, if this identity is mono-dimensional-focusing only on sport practice and excluding other personal aspects-when sport abandonment occurs, it can lead to the suffering of psychiatric symptoms and burnout, both in young people and in adults (Giannone et al, 2017;Chang et al, 2018;Gustafsson et al, 2018b). As a consequence, especially for children and adolescents, on the one hand, it is essential to develop an identity as an athlete that allows them to feel competent and autonomous and maintain positive relationships with their peers; on the other hand, to prevent negative consequences in case of sport abandonment (either relative or definitive), such an identity should not be mono-dimensional, being preferably focused on their overall development as athletes rather than exclusively linked to their competence in a specific sport (Coakley, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Past research adopting the Smith (1986) burnout model generally supported the link between stress and athletic burnout (Tabei et al, 2012;Chyi et al, 2017;Chang et al, 2018). It is imperative to understand the moderators/mediators underlying the stress-burnout relationship so that practitioners can use this knowledge to help athletes avoid burnout .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, under high life stress conditions, athletes with high resilience and coaches' high tangible social support were less susceptible to burnout than those with high resilience but low coaches' tangible social support. Recently, Chang et al (2018) used a twowave, time-lagged survey to examine the moderating effects of psychological flexibility on the athletic identity-burnout relationship. They found that high athletic identity athletes with low psychological flexibility developed emotional exhaustion (one factor of burnout) over time, but high athletic identity with high psychological flexibility was negatively associated with emotional exhaustion over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation